The Question of Diplomatic Mission of Czechoslovakia in Lithuania in 1921-1939 - Dalia Bukelevičiūtė (Lietuvos Istorijos Studijos)
The problem of diplomatic relations between Lithuania and Czechoslovakia is that Lithuanian historiography has not been investigated yet. There are very important L Švec works from the Czech historians. The base of this article is material from Lithuania and Czech Republic archives.